Designing an English course for tourism at State Amazonian University - García-León, Erika Paola; Almache-Granda, Gabriela Katherine (Dominio de las Ciencias, 2019)
The purpose of the investigation were to propose an ESP course for students at Universidad Estatal Amazonica in the Department of Life Sciences in Tourism Engineering Puyo, Pastaza- Ecuador. This proposal consists in a Communicative Syllabus with specific topics and grammar structure, which will allow the learners to develop their abilities in English communication. It was organized in four units with the same structure divided into four lessons: a vocabulary lesson, a grammar lesson, a professional lesson and a case study. It was designed to be taught in 64 hours face-to-face and 4 weekly practical hours. he proposal was created to ensure the students get the necessary vocabulary and grammar focused on tourism in English linguistic structures and that they can improve their and oral and written expression speaking as well as them to perform activities related to their field of specialization. As a form of evaluation, the continuous evaluation and final exam were proposed to determine academic progress.